Pemisahan Harta dalam Perjanjian Perkawinan (Marriage Agreement) Studi Kasus di Kota Pekanbaru: Penelitian - Syahrial; Maya Intan Pratiwi; Nining Suniarti (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2025)
The main problem in this study is how the separation of assets in a marriage agreement in Pekanbaru City and what are the obstacles to the separation of assets in a marriage agreement. The research method is Empirical Juridical Legal Research by means of a survey. This research is descriptive analytical, namely providing a clear and detailed description of an event that occurred. From the results of the study it can be concluded, First, Separation of assets in a marriage agreement in Pekanbaru City must be made with a notarial deed carried out before a notary, made by the parties, namely the prospective husband and wife or husband and wife before a notary, while the contents of the marriage agreement must state that the separation of assets must not be contrary to Islamic law and the provisions of applicable laws and regulations, while regarding the marriage agreement including the separation of assets of husband and wife at this time is officially recorded at the Office of Religious Affairs (KUA). Therefore, a notary has very important authority in making a marriage agreement because a notary is authorized to make an authentic deed as stated in Article 15 Paragraph 1 of the UUJN. Second, Obstacles in the separation of assets in a marriage agreement are the husband and wife acting in bad faith in terms of debts to third parties, the prospective husband or wife violating the contents of the marriage agreement, during the marriage the husband or wife violating the contents of the marriage agreement, a civil dispute occurs regarding the contents of the marriage agreement, the agreement can only be changed with the consent of both husband and wife, and does not harm the interests of third parties, and is authorized by a marriage registrar. Not many people are willing to sign a marriage/prenuptial agreement. So far, a prenuptial agreement is considered only to separate or mix the assets of husband and wife. As a result, the party who proposes it is considered by society as a 'stingy' person.